Stem Cell in Breast Cancer Theraphy - Kartika, Juspeni; Legiran (Clinical and Research Journal in Internal Medicine, 2024)
There is a lot of research to support that cancer stem cell attract normal stem cell. The tendency of tumor cells to attract stem cells then becomes the basis for the use of stem cells in breast cancer theraphy. When neural stem cell applied as a carrier, it will make the amount, timing, and location of viral oncolytic or drug release can be precisely controlled. Finally, this situation will increase the effectiveness of breast cancer therapy and reduce side effects. This is a brief review about potency of stem cell as breast cancer treatment. This article aim to increased our knowledge about the potency of stem cell as breast cancer treatment. The tendency of tumor cells to attract stem cells then becomes the basis for the use of stem cells as enzyme/prodrug theraphy, secreted agent, viral oncolytic carrier or nanoparticle (drug) carrier which tends to be more localized around the tumor. When neural stem cell applied as a carrier, it will make the location, amount and timing of drug release or viral oncolytic can be precisely controlled.